2016
DOI: 10.1007/s10096-016-2866-7
|View full text |Cite
|
Sign up to set email alerts
|

Gonorrhea infection increases the risk of prostate cancer in Asian population: a nationwide population-based cohort study

Abstract: This nationwide population-based retrospective cohort study evaluated the risk of developing prostate cancer among patients with gonorrhea. We identified cases of newly diagnosed gonorrhea in men between 2000 and 2010 from the Taiwan National Health Insurance Research Database. Each patient with gonorrhea was matched to four controls, based on age and index year. All subjects were followed up from the index date to December 31, 2010. The Cox proportional hazards regression model was used to assess the risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…However, the data display significant heterogeneity, which limits the validity of conclusions. Two cohort studies have suggested that Neisseria gonorrhoeae infections increase the risk of PCa [95,96]. In one study, HPV detection was more frequent in PCa specimens compared with specimens retrieved from nonmalignant tissue, which was not confirmed by other authors [97,98].…”
Section: Sexual Activity and Risk Of Pcamentioning
confidence: 89%
See 1 more Smart Citation
“…However, the data display significant heterogeneity, which limits the validity of conclusions. Two cohort studies have suggested that Neisseria gonorrhoeae infections increase the risk of PCa [95,96]. In one study, HPV detection was more frequent in PCa specimens compared with specimens retrieved from nonmalignant tissue, which was not confirmed by other authors [97,98].…”
Section: Sexual Activity and Risk Of Pcamentioning
confidence: 89%
“…Experimental studies and in vitro models have shown possible mechanisms linking smoking and PCa progression, such as increased heme-oxygenase-1 messenger RNA expression, which may play a role in tumor angiogenesis [50,64,73,78,79,95]. An effect of smoking on tumor progression through hypermethylation of genes has also been suggested [80,97].…”
Section: Poorer Response To Treatmentmentioning
confidence: 99%
“…Wang et al conducted a study of 355 men with gonorrhea and 1420 controls and found that gonorrhea resulted in a 5-fold increased risk of PCa. [19] Meanwhile, gonorrhea infection is one of the major causes of epididymo-orchitis. [22] However, the possible mechanisms of PCa and the potential roles of asymptomatic prostatic inflammation and epididymo-orchitis require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The NHIRD uses International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM) codes to record diagnoses. All diagnoses of prostate diseases were made by board‐certified urologists, and all diagnoses of CP given by dentists 10,11 . Bureau of NHI randomly reviews the records of 1 in every 100 ambulatory care visits and 1 in every 20 in‐patient claims to verify the accuracy of the diagnoses (Bureau of National Health Insurance Regulations) 12 .…”
Section: Methodsmentioning
confidence: 99%